The Impact of Indonesian Army Information and Data Processing Service Department Programming Training for Indonesian Army - Rizal Mutaqin; Ghani Mutaqin; Fitry Taufiq Sahary; Dwi Shinta Dharmopadni (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2023)
This research discusses the importance of programming training for soldiers of the Indonesian Army in facing the era of globalization and digital transformation. In this context, programming is recognized as a tool for developing creative and logical thinking skills, which are key in overcoming complex challenges both in the military and society. The purpose of this study was to determine the impact of programming training for Indonesian Army soldiers. The methodological approach used combines quantitative and qualitative methods, through an initial survey to identify the number of soldiers taking programming training as well as an in-depth interview approach to explore the impact of programming on military assignments. The results showed that programming training had a positive impact, not only on improving problem-solving skills but also on the development of logical, systematic thinking and analytical skills. From a military perspective, programming gives The Indonesian Army soldiers a competitive edge in addressing modern challenges, such as technology development, intelligence analysis, and data management. Programming training also forms habits of logical thinking that are useful in making everyday decisions. Therefore, programming is not only a technical skill but also a tool to deal with the changing dynamics of future battles and adapt to technological developments.